About factors related to the occurrence of earthquakes in the Song Tranh 2 hydropower area in period 2011-2014 - Duan, Bui Van; Giang, Ha Thi; Duong, Nguyen Anh; Nguyen, Pham Dinh (Vietnam Journal of Earth Sciences, 2016)
This article focuses on analysis of the relationship between the occurrence of earthquakes in Song Tranh 2 reservoir area in period 2011-2014 and factors: (1) Fault locations and features in the reservoir area; (2) The incremental stress caused by reservoir loads; (3) The slip-tendency of faults in the reservoir area. Methods of analysis of geological maps, tectonic documents, earthquake data; calculation of incremental stress caused by reservoir loads; assessment of the effects of oscillating reservoir loads on major faults; the slip-tendency analysis on a fault surface are used for this goal. The obtained results indicate that the aforementioned factors have interacted with each other and significantly contributed to the occurrence of earthquakes in the study area. Faults of NW-SE directions within the reservoir area have the advantageous location and mechanism for slip process when they are affected by oscillating reservoir loads. Moreover, reservoir loads have significantly increased stress of rocks under the bottom of the reservoir. These provide explainations for the fact that most reservoir-induced earthquakes occurred in the Song Tranh 2 hydropower reservoir area (including event M4,7 occurred on 15 December 2012) are ralated to the activity of faults of NW-SE directions. References Bell M.L. & Nur A., 1978: Strength changes due to reservoir-induced pore pressure and stresses and application to Lake Oroville. J. Geophys. Res. 83, p.4469-4483. Carder D.S., 1970: Reservoir loading and local earthquakes, in engineering seismology-the works of man, Geol. Soc. Am. Eng. Geol. Case Histories 8, p. 51-61. Nguyen Van Giang, Jan Wiszniowski, Beata Plesiewicz, Grzegorz Lizurek, Dinh Quoc Van, Le Quang Khoi, 2015: Some Characteristics of Seismic Activity in the Song Tranh 2 Reservoir, Quang Nam, Vietnam by Local Seismic Network Data. Earth Sciences.Vol. 4, No. 3, 2015, p.101-111 Gough D.I. & Gough W.I., 1970a: Stress and deflection in the lithosphere near Lake Kariba. Geophys. J.R. Astro. Soc. 21, p.65-78. Gough D.I. & Gough W.I., 1970b: Load induced earthquakes at lake Kariba-II. Geophys. J.R. Astro. Soc. 21, p.79-101. Gupta H.K., Rastogi B.K., Narain H., 1972a: Common features of the reservoir associated seismic activities. Bull. Seismol. Soc. Am. 62, p.481-492. Gupta H.K., Rastogi B.K., Narain H., 1972b: Some discriminatory characteristics of earthquakes near the Kariba, Kremasta and Koyna artificial lakes. Bull. Seismol. Soc. Am. 62, p.493-507. Lường Thị Thu Hoài, Nguyễn Văn Vượng, Bùi Văn Đông, 2014: Đặc điểm đứt gãy và mối quan hệ với động đất kích thích khu vực hồ chứa thủy điện Sông Tranh 2, huyện Bắc Trà My, tỉnh Quảng Nam. Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ, Tập 30, Số 2S, tr.21-32. Phạm Văn Hùng, 2001: Đặc điểm hoạt động của các đứt gãy kiến tạo ở rìa Bắc địa khối Kon Tum. Tạp chí Các Khoa học về Trái đất. T.24, (4), tr.370-377. Phạm Văn Hùng, 2004: Đặc điểm chuyển động của đứt gãy Sông Bung - Trà Bồng trong Kainozoi. Tạp chí Các khoa học về Trái đất, T.26, (4PC), tr.447-453. Phạm Văn Hùng, 2010: Đánh giá hiện trạng và khoanh vùng cảnh báo nguy cơ nứt đất tỉnh Quảng Nam. Tạp chí Các Khoa học về Trái đất, T.32, (4), tr.348-356. Lê Huy Minh, 2012: Kết quả khảo sát động đất tháng 9/2012 khu vực thủy điện Sông Tranh 2. Nghiên cứu và phát triển công nghệ - Điều tra cơ bản, website Viện Hàn lâm KH&CN Việt Nam (http://www.vast.ac.vn/...). Morris A., Ferril D. & Henderson D., 1996: Slip-tendency analysis and fault reactivation. Geology 24, p.275-278. Neves M., Paiva L. & Luis J., 2009: Software for slip-tendency analysis in 3D: A plug-in for Coulomb. Computers & Geosciences, 35, p.2345-2352. Phạm Đình Nguyên (chủ biên), 2014: Báo cáo khảo sát, nghiên cứu đứt gãy, động đất và núi lửa. Dự án nhà máy điện hạt nhân mới ở Việt Nam địa điểm Quảng Ngãi. Giai đoạn nghiên cứu tiền khả thi. Quyển số 1.1; Lưu trữ Viện Vật lý Địa cầu; 61tr. Nikolaev N.I., 1974: Tectonic conditions favourable for causing earth quakes occurring in connection with reservoir filling. InsSeismic ef fects of reservoir impounding; de JUDD,W.R.,Eng. Geol., 3 (1-2), p.171-139. Nguyễn Ngọc Thủy (chủ biên), 2003: Báo cáo Đánh giá độ nguy hiểm động đất ở khu vực công trình thủy điện Sông Tranh 2. Giai đoạn phục vụ lập báo cáo nghiên cứu khả thi. Lưu trữ Viện Vật lý Địa cầu. Nguyễn Thanh Tùng và Bùi Văn Duẩn, 2007: Đánh giá trường ứng suất gia tăng, độ lún lòng hồ và động đất kích thích khu vực hồ chứa thủy điện Hoà Bình. Báo cáo chuyên đề thuộc đề tài NCKH&PTCN cấp NN mã số ĐTĐL - 2005/19G. Nguyễn Đình Xuyên, Nguyễn Thanh Tùng, Trần Dương Trí, Bùi Văn Duẩn, 2005: Sự thay đổi trường ứng suất, biến dạng và khả năng phát sinh động đất kích thích khu vực hồ chứa Sơn La. Báo cáo đánh giá tác động môi trường. Lưu trữ Viện Vật lý Địa cầu. Qiu X., 2012: Factors controlling the occurrence of reservoir-induced seismicity. Proceedings of 1st Civil and Environmental Engineering Student Conference, Imperial College London, 25-26 June 2012. Qiu X. & Fenton C., 2015: Factors Controlling the Occurrence of Reservoir-Induced Seismicity. In: Lollino G., Giordan D., Thuro K., Carranza-Torres C., Wu F., Marinos P., Delgado C. (eds.), Engineering Geology for Society and Territory - Volume 6: Springer International Publishing, Cham, p.567-570. Rajendran K., 1995: Sensitivity of a Seismogenic Reservoir to Low Amplitude Fluctuations - Observations from Lake Jocassee, South Carolina, Pure and Applied Geophysics, Vol.145, p.87-95. Roeloffs E.A., 1988: Fault stability changes induced beneath a reservoir with cyclic changes in water level. J. Geophys. Res. 93, p.2107-2124. Talwani P., 1997b: On the nature of reservoir - induced seismicity. Pure Appl. Geophys. 150, p.473-492. Nguyễn Văn Trang (chủ biên), 1996: Bản đồ địa chất và khoáng sản Việt Nam, tờ Hội An (D-49-I) và tờ Bà Nà (D-48-VI) tỷ lệ 1:200.0000. Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Nguyễn Văn Trang (chủ biên), 1997: Bản đồ địa chất và khoáng sản Việt Nam, tờ Quảng Ngãi (D-49-VII và D-49-VIII) và tờ Đắk Tô (D-48-VII), tỷ lệ 1:200.0000. Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Trần Dương Trí, 2004: Chương trình tính toán độ lún đàn hồ và ứng suất gia tăng của đất đá dưới đáy hồ chứa theo bài toán 2D và 3D trong môi trường Matlab (Incremental Stress and Deflection in the 2D and 3D Lake). Lưu trữ Phòng Địa chấn, Viện Vật lý Địa cầu, Hà Nội. Cao Đình Triều, Đinh Quốc Văn, Bùi Anh Nam, Hà Vĩnh Long, 2013: Một số kết quả nghiên cứu bước đầu về động đất kích thích hồ thủy điện Sông Tranh 2. Tạp chí Địa chất, loạt A, số 333, 1-2/2013, tr.1-14. Phan Trọng Trịnh, 2012: Lịch sử động đất kích thích liên quan tới hồ chứa. Tin khoa học - công nghệ trong nước, website Viện Hàn lâm KH&CN Việt Nam (http:// www.vast.ac.vn/...). Toda S., Stein R.S., Sevilgen V., and Lin J., 2011: Coulomb 3.3 graphic-rich deformation and stress-change software-user guide: U.S. Geological Survey Open-Report 2011-1060, XX p. Wiszniowski J., Giang N.V., Plesiewicz B., Lizurek G., Van D. Q., Khoi L. Q., and Lasocki S., 2015: Preliminary results of anthropogenic seismicity monitoring in the region of Song Tranh 2 reservoir, Central Vietnam. Acta Geophysica, Vol 63, no.3, p.843-862. http://gdem.ersdac.jspacesystems.or.jp/ http://www.geomapapp.org/